2012
DOI: 10.4021/jmc440w
|View full text |Cite
|
Sign up to set email alerts
|

Symmetrical Trimalleolar Fractures of the Bilateral Ankles: A Case Report

Abstract: A rare case of symmetrical trimalleolar fractures of bilateral ankles has been described. A 54-year-old man fell off a motorbike on a snow covered road with inversion of bilateral ankle joints symmetrically, and sustained symmetrical trimalleolar fractures of bilateral ankles. The patient underwent osteosyntheses on bilateral ankles and the post-operative course was uneventful. The patient had no complaints at 5 years following surgery. Probable mechanism of the fracture is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 3 publications
2
2
0
Order By: Relevance
“…14,17 We found that they are the most commonly reported rotational ankle injuries in literature along with our cases (1,4). 13 Nagasawa et al reported a similar presentation to our case 2 in term of mechanism of injury, however, their patient sustained an SER IV instead. 13 It is originally described that SER IV and PER IV are different from each other in terms of level of fractured fibula being low in SER and higher in PER.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…14,17 We found that they are the most commonly reported rotational ankle injuries in literature along with our cases (1,4). 13 Nagasawa et al reported a similar presentation to our case 2 in term of mechanism of injury, however, their patient sustained an SER IV instead. 13 It is originally described that SER IV and PER IV are different from each other in terms of level of fractured fibula being low in SER and higher in PER.…”
Section: Discussionsupporting
confidence: 76%
“…13 Nagasawa et al reported a similar presentation to our case 2 in term of mechanism of injury, however, their patient sustained an SER IV instead. 13 It is originally described that SER IV and PER IV are different from each other in terms of level of fractured fibula being low in SER and higher in PER. [1][2][3] Haraguchi et al found in their biomechanical study that low fibular fracture can be found in reproduced PER mechanism on cadavers.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations